Quality in the hospital attention to the newborn - Rosa, Michelly Kim de Oliveira; Gaíva, Maria Aparecida Munhoz (Rev Rene, 2009)
Quality comprises several areas and sectors of health. Once it is a complex subject, the quality evaluation has different dimensions and the ones which are the most used by the health services are those that involve structure, processes and results. We aimed at refl ecting on the quality and use of evaluation criteria in the scope of newborn assistance. It is a matter of bibliographic review on the subject, on a theorical-refl exive perspective. The quality of attention to the new-born is based on the history of the new-born assistance institutionalization, on the health services structure, human resources, materials and technological procedures. There are different perspectives of evaluating the new-born assistance quality, including the use of the mortality index as well as and other specifi c assistance indexes. The offered discussion shows the use of evaluative practices importance and necessity of implementation, in the search for quality health services in neonatology.